EFFECT OF GELATIN AS A BINDER ON TURMERIC EXTRACT TABLET FORMULATION - Adi Permadi; Iis Wahyuningsih; Sapto Yuliani; Ibdal Satar; Ratna Wijayatri (Universitas Muhammadiyah Magelang, 2022)
In line with the progress of the times in which all aspects of many products are made easy and comfortable for the wearer. The main components for tablet formulations are the fillers, binders, crushers, thinners and lubricants. Among these components, the binders play a key role on the powder cohesion properties during the formation of tablet granules. Due to the effect of gelatin on the tablet properties are positive significant, therefore, this work tries to evaluate the effect of gelatin in the different formulation on the turmeric extract tablets. In this study, turmeric extract tablets were formulated using 15 g of turmeric extract, 35 g of aerosil, 12.8 g of lactose, 1% magnesium stearate, 200 ml of aquadest and gelatin as a binder. To evaluate the effect of gelatin on the tablet formulation, the gelatin was then prepared in different formulation namely 0.1 g (formulation A), 0.2 g (formulation B) and 0.5 g (formulation C), respectivley. Based on the tablet properties, the turmeric tablet with formulation C met the standard requirements of friability less than 1%, the hardness in the range of 4 -8 kg and disintegration time under 15 minutes.